Efficacy Assessment of Garlic Extract and Rabbit Urine as a Natural Aphid Control Agent on Infested Tomato Plants - David Beckham Isooba (Uganda Christian University, 2025)
This experiment aimed to assess the effectiveness of garlic extract and rabbit urine concoction as a natural aphid control agent on infested tomato plants (Solanum lycopersicum). The study investigated the impact of different doses of garlic extract on plant height, leaf damage, Number of aphids and Number of flowers at the flowering stage. The garlic extract was prepared by crushing garlic bulbs and sieved to achieve the desired concentrations after mixing it with the desired concentrations of rabbit urine. The experiment employed a randomized complete block design with four treatment groups each replicated three times: a control group (0%), low dose (10%), medium dose (30%), and high dose (50%) of the mixture concentration of rabbit urine and garlic extract concoction. The treatments were applied using a handheld sprayer, and the plants were monitored for aphid populations using visual inspection. Data collected were subjected to statistical analysis, including analysis of variance (ANOVA), to determine significant differences between treatments. The results revealed that higher doses of garlic extract and rabbit Urine concoction led to increased plant height, decrease in leaf damage caused by aphids, , and reduced number of aphids as well as increased number of flowers. The control group exhibited the lowest values for all parameters, while treatments with garlic extract and rabbit urine concoction showed significant improvements. The highest yields were observed in Treatment 50%, where plants treated with the highest dose of garlic extract and rabbit urine concoction had the highest plantt height, least number leaves damaged by aphids and highest number of flowers at flowering stage. These findings demonstrate the potential of garlic extract and rabbit urine concoction as an effective aphid control agent, capable of enhancing tomato crop health and growth and economic returns for farmers.
Undergraduate